De Novo Extra-Thyroidal Manifestations of Graves’ Disease presenting 16 Years after Total Thyroidectomy for Thyroid Cancer - Kwee, Ann; Yong, Kai-Ling; Seah, Lay Leng; Chng, Chiaw-Ling (Journal of the ASEAN Federation of Endocrine Societies, 2022)
We present a 61-year-old Chinese female who had a history of angioinvasive follicular thyroid cancer (FTC) treated with total thyroidectomy 16 years ago, without radioactive iodine (RAI) treatment who now presents with de novo pretibial myxedema (PTM) followed by active severe Graves’ ophthalmopathy (GO) requiring pulse steroids and radiotherapy.